Reasoning Web. Semantic Technologies for Information Systems 5th International Summer School 2009, Brixen-Bressanone, Italy, August 30 - September 4, 2009, Tutorial Lectures - Tessaris, Sergio; Franconi, Enrico; Eiter, Thomas; Gutierrez, Claudio; Handschuh, Siegfried; Rousset, Marie- Christine; Schmidt, Renate (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2009)
This book contains a collection of seven thoroughly revised tutorial papers based on lectures given by leading researchers at the 5th International Summer School on the Reasoning Web, held in Brixen-Bressanone, Italy, from August 30 to September 4, 2009. The objective of the book is to provide a coherent introduction to semantic web methods and research issues with a particular emphasis on reasoning. The focus of this year's event was on the use of semantic technologies to enhance data access on the web. Topics covered include design and analysis of reasoning procedures for description logics; answer set programming basics, its modeling methodology and its principal extensions tailored for semantic web applications; languages for constraining and querying XML data; RDF database theory and efficient and scalable support for RDF/OWL data storage, loading, inferencing and querying; tractable description logics and their use for ontology-based data access; and the social semantic desktop, which defines a user's personal information environment as a source and end-point of the semantic web.